Development of low-cost material measures for calibration of the metrological characteristics of areal surface texture instruments. Issue 1 (2015) - Leach, Richard; Giusca, Claudiu; Guttmann, Markus; Jakobs, Peter-Jürgen; Rubert, Paul
Abstract: In this paper, the development of a number of material measures, which are designed to allow users to calibrate areal surface texture instruments, is presented. The material measures include grid structures, for the determination of the amplification, linearity and squareness of the x, y and z -axes, and star patterns, for the determination of the lateral period limit. Relatively complex methods of manufacture have been used to produce master artefacts, which are then replicated to produce cost-effective material measures for users. The process chain for the material measures is presented along with the methods used to calibrate them.